Determinants of Income Inequality Villages and Cities in Indonesia - Juniati, Wike; Abdullah, Muhammad Latif; Wibowo, Muhammad Ghafur (Universitas Airlangga, 2022)
The image of development in Indonesia is getting worse when development progress is felt by the upper class. The segmentation of the upper and lower levels of society is reflected in the gap between life in the village and the city. The purpose of this study is to analyze the determinants of income inequality based on the classification of villages, cities, and between villages and cities in Indonesia. The data analysis method used is panel data regression which is an analytical technique that is observed over a certain period. The data used is annual secondary data from 2016-2020 in 34 provinces of Indonesia. Inequality analysis is carried out by calculating the Gini index based on household expenditure data. Economic growth, population, human development index, domestic investment, technology development index, and employment opportunities are independent variables. The results of this study found that there was a significant negative relationship the technology development index and positive relationship population in city and between village and city areas. Then the variable employment opportunity have a significant negative relationship to income inequality in the village.